Why are CGRP monoclonal antibodies not yet the first line treatment in migraine prevention? - Simioni, Caio Vinicius de Meira Grava (Arquivos de Neuro-Psiquiatria, 2022)
Migraine is a prevalent disorder and a cause of high disability, influenced by modifiable and non-modifiable risk factors. Comorbid and psychiatric illnesses are prevalent in migraine patients and should be considered when choosing preventive drugs. There have been unforeseen problems with the use of preventive treatment of migraine with oral drugs, mainly due to side-effects that cannot be tolerated and lack of efficacy, leading to high discontinuation rates. Anti-CGRP monoclonal antibodies (mAbs) have shown better tolerance profiles, based on the low dropout rates in clinical trials due to adverse events. First-line therapy is a term most expressed in some medical specialties that adopt standardized protocol treatments and may not be suitable for treating migraine. Regarding efficacy, mAbs don’t seem to perform much better than the current prophylactic oral drugs in reduction of monthly migraine days compared to placebo. Monoclonal antibodies against CGRP pathway have been prescribed recently, which raises some concern about their safety in the long term. Only side effects observation will confirm whether CGRP blockade causes susceptibility to severe side-effects, at least to specific subpopulations. CGRP may play a role in regulating uteroplacental blood flow and myometrial and uterine relaxation, as well as blood pressure control, raising the suspicion that its blockade could cause complications during pregnancy. Recent guidelines retain the recommendation of starting preventive treatment of migraine with oral drugs. Both the fact that it is new and costs are the reason why guidelines recommend the prescription of mAbs only after failure of at least two oral drugs.
Keywords: Antibodies, Monoclonal; Costs and Cost Analysis; Efficacy; Health Services Needs and Demand; Migraine Disorders; Headache; Pharmaceutical Preparations; Prescriptions; Safety; Surveillance; Therapeutics